The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1478-4491-11-53
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward working in rural areas of Thai medical, dental and pharmacy new graduates in 2012: a cross-sectional survey

Abstract: Background: Inequity in health workforce distribution has been a national concern of the Thai health service for decades. The government has launched various policies to increase the distribution of health workforces to rural areas. However, little is known regarding the attitudes of health workers and the factors influencing their decision to work in rural areas. This study aimed to explore the current attitudes of new medical, dental and pharmacy graduates as well as determine the linkage between their chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 14 publications
(15 reference statements)
4
61
1
Order By: Relevance
“…Rural upbringing and entering the nursing education program by local recruitment were found to be associated with a more positive attitude toward rural areas in this study, and that finding is similar to studies with newly graduated doctors in Thailand and in other low-middle income countries (LMICs) [8, 9]. These studies found that students admitted to medical school through a special quota for rural background students preferred to work in community hospitals in rural areas, and students who have spent a significant period of time in rural settings were more likely to practice in their home country and in rural areas.…”
Section: Discussionsupporting
confidence: 87%
“…Rural upbringing and entering the nursing education program by local recruitment were found to be associated with a more positive attitude toward rural areas in this study, and that finding is similar to studies with newly graduated doctors in Thailand and in other low-middle income countries (LMICs) [8, 9]. These studies found that students admitted to medical school through a special quota for rural background students preferred to work in community hospitals in rural areas, and students who have spent a significant period of time in rural settings were more likely to practice in their home country and in rural areas.…”
Section: Discussionsupporting
confidence: 87%
“…Six of the eleven articles were from Australia, two from South Africa and one from the United States, India and Thailand …”
Section: Resultsmentioning
confidence: 99%
“…Only two studies were conducted in middle-income countries: South Africa and Thailand 33,34. Three articles explored the influence of rural origins of dental students/graduates,3234 while the other four articles investigated the impact of special didactic programs or rural placements after graduation 28–31. It should be noted that the definition of “rural” varied across studies.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the definition of “rural” varied across studies. For instance, McMillan and Barrie defined “rural” in South Africa as any administrative area that was smaller than a town or city,33 whereas Thammatacharee et al considered the term “rural” to refer to all districts, other than provincial capitals, in all Thai provinces outside Greater Bangkok 34. All the selected articles demonstrated some degree of bias, as they were conducted in uncontrolled settings where randomization was not feasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation